In-situ self-reinforcement of amorphous polylactide (PLA) through induced crystallites network and its highly ductile and toughened PLA/poly (butylene adipate-co-terephthalate) (PBAT) blends - Eraslan, Kerim; Altinbay, Aylin; Nofar, Mohammadreza (ELSEVIER, 2024)
Crystallites of a semicrystalline polylactide (cPLA) were induced in an amorphous PLA (aPLA) and its blends with poly(butylene adipate-co-terephthalate) (PBAT) to achieve in-situ self-reinforced PLA based structures. The approach involved the melt blending of cPLA as a minor phase with aPLA and its blends with PBAT at processing temperatures below the crystal melting peak of cPLA. An injection molding (IM) process was first adopted to obtain self-reinforced PLA (SR-PLA) structures at aPLA/cPLA weight ratios of 100/0, 95/5, 90/10, 85/15, and 80/20. IM barrel and mold temperatures revealed crucial impacts on preserving the cPLA crystallites and thereby enhancing the final mechanical performance of SR-PLA (i.e., aPLA/cPLA) samples. SR-PLA samples at various aPLA/cPLA weight ratios of 100/0, 90/10, 80/20, and 70/30 were then melt blended with PBAT to produce SRPLA/PBAT at a given ratio of 85/15. These blends were first prepared in an internal melt mixer (MM) to evaluate the rheological properties. The rheological analysis confirmed the significance of cPLA reinforcing efficiency within SR-PLA and its corresponding blends with PBAT. Similar SR-PLA/PBAT blends were also prepared using the IM process to explore their thermal and mechanical characteristics. The effect of cPLA concentrations in blends was distinctive, leading to significant enhancements in stain at break and toughness values. This was due to the increased crystallite network within the matrix, further refining PBAT droplets. Morphological analysis of the melt-processed blends through MM and IM also revealed that the PBAT droplets were further refined when the IM process was applied. The induced shear during the molding could have further elongated the cPLA crystallites towards a fiberlike structure, which could additionally cause the matrix viscosity to increase and refine the PBAT droplets.
Keywords: Polylactide; Induced crystallization; Self -reinforcing; PLA/PBAT blend; Rheology; POLY(LACTIC ACID) COMPOSITES; MECHANICAL-PROPERTIES; SILICATE NANOCOMPOSITES; FOAMING BEHAVIOR; COPOLYMERS; LACTIDE; FIBER; Biochemistry & Molecular Biology; Chemistry; Polymer Science